Overweight might Affect the Live Birth Rate after Frozen Thawed Embryo Transfer Cycles in Chinese Women - Meihong Cai; Sushi Jiang; Xiaohuan Luo; Yaqiao Zhu; Wei Wang; Yaya Peng; Wei Xia (IMR Press, 2023)
Background: Overweight affects about 34.3% of Chinese adults, especially women of childbearing age. The purpose of this study was to investigate whether overweight affect the live birth rate of frozen-thawed embryo transfer (FET) cycles in Chinese mothers. Methods: This retrospective case-control study was conducted in all patients undergoing FET cycles from May 2016 to October 2020 at a single center. A total of 969 FET cycles performed in 632 patients were included in the analysis. Patients were divided into the four groups based on the mother's body mass index (BMI): Group 1: BMI <18.5 kg/m2; Group 2: 18.5 kg/m2 ≤ BMI <24 kg/m2; Group 3: 24 kg/m2 ≤ BMI <28 kg/m2; Group 4: BMI ≥28 kg/m2. The main outcome indicator was the live birth rate per FET cycle. The secondary endpoints included rates of biochemical clinical pregnancy, clinical pregnancy, implantation, multiple pregnancy and miscarriage. Results: Ovarian reserve parameters were similar among the four groups (p = 0.382 for anti-Müllerian hormone and p = 0.195 for antral follicle count). Additionally, the rates of chemical pregnancy, clinical pregnancy, implantation and live birth were comparable in the four groups. Pregnancy outcomes were similar among the four groups using logistic regression analysis adjusting for age, anti-Müllerian hormone (AMH), antral follicle count (AFC), endometrial thickness, indication combined with polycystic ovarian syndrome (PCOS), duration of infertility (years), stage of embryos transferred, previous attempts, protocol of endometrial preparation, number of embryos transferred, and BMI. A decreasing tendency in the rates of clinical pregnancy (p = 0.032) and live birth (p = 0.011) with BMI change was observed through Chi Square for Trend test. Conclusions: Overweight might reduce the possibility of live birth after FET cycles in Chinese mothers.